PENGARUH KEGIATAN KELOMPOK KERJA GURU (KKG) DAN MOTIVASI KERJA TERHADAP INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR DI WILAYAH II KABUPATEN REJANG LEBONG - Sangkan Hidayat Darmawan (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2018)
The arm of the study where  (1) To investigate  wheter or not there  was a significant influence between  KKG PAI at elementary school toward  learning  inovation in area  II Rejang Lebong  Regency.  (2) To investigate  wheter  or not there  was a significant influence  between  work motivation toward  learning  inovation in area  II Rejang Lebong  regency.  (3) To investigate wheter or not there was a significant influence of KKG and Work motivation toward religion in area II Rejang Lebong Regency. Mhetod  use in this study  was descriptive  quantitative by applying  field research  42 religion teachers  at elementary school  in area  II Rejang Lebong  were the population. Simple linier regresion  and  doubel  liniear regresion  were used as the technique of data  analisys  by aplying SPSS  version  16.0  the finding revealed  that the contribution of teachers  work group  (KKG) toward religion inovation wa 27,2  % and  the contribution of religion work motivation was 0,96%.  The contribution between  teachers work group (KKG) (X1) and work motivation (X2) gave positive and significant influence toward learning inovation (Y) in area II Rejang Lebong regency as equal 25,4 % in conclusion there were significant influence between  teachers  work group and work motivation toward  learning inovation at elementary school religion in area  II Rejang Lebong  Regency